Working Models of Attachment Shape Perceptions of Social Support Evidence From Experimental and Observational Studies. [article]. - Collins, Nancy L.
Two studies the association between attachment style and perceptions of social support. Study 1 (N=95 couples) used and experimental paradigm to manipulate social support in the context of a stressful task. Insecure participants (anxious and avoidant) who received low-support messages appraised these messages more negatively, rated a prior behavioral interaction with their partner as having been less supportive, and performed significantly worse at their task compared with secured participants. Study 2 (N=153 couples) used similar paradigm except that partners were allowed to send genuine support messages. Insecure participants (especially fearful) perceived their partners' messages as less supportive, evn after controlling for independent ratings of the messages and relationship-expectations. These studies provide evidence that individuals are predisposed to appraise their support experiences in ways that are consistent with their chronic working models of attachment, especially when the supportmessage is ambiguous. (from the author)